THE EFFECT OF GROUP INVESTIGATION METHOD ON STUDENTS’ WRITING ACHIEVEMENT - Renol Aprico Siregar; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2015)
The objective of the study was to find out the effect of Group Investigation method on students’ writing achievement on narrative text. The study was conducted by using experimental research design. The population of this study was eight classes of the eleventh grade students of SMA Negeri 1 Kotapinang. The samples were taken by using clustering technique and two of the eight classes which was consisted of 60 students used as the samples, one class as experimental group and the other class as control group. In the treatment, the experimental group was taught by using Group Investigation method, the control group was taught without using Group Investigation method. Writing narrative text test was used as the instrument for collecting the data. Therefore, after analyzing the data, it was found that the value of  was 3.02 with the degree of freedom (df) = 58 at that level of significance (α=0.05) = 2.00. It means that  was considerably higher than  (3.02 > 2.00). The result of this study shows Group Investigation method has a significant effect on students’ achievement in writing report text. Key words : Group Investigation, Narrative text, Writing achievement